The Sputum Microbiome in Chronic Obstructive Pulmonary Disease Exacerbations - Huang, Yvonne J. (Ann Am Thorac Soc, 2015)
Acute exacerbations of chronic obstructive pulmonary disease (COPD) are thought to be associated with—and perhaps to mediate—accelerated loss of lung function in COPD. Although the application of culture-independent methods for detection of bacteria have shown COPD to be associated with marked differences in the burden, diversity, and composition of the bronchial bacterial microbiome, few studies have examined the changes associated with community-acquired exacerbations of the disease. In a longitudinal cohort study of COPD, the availability of sputum samples from subjects obtained at the onset of an exacerbation and during periods of clinical stability before and after the event enabled us to recently address this gap in knowledge, using culture-independent, 16S rRNA–based analysis methods combined with in silico inference of metagenomic functions. We observed sputum bacterial composition to be generally stable over the preexacerbation period of clinical stability, but to change at the time of exacerbation, with specific enrichment in not only typical COPD-associated bacterial species (e.g., Haemophilus influenzae) but also other phylogenetically related species with pathogenic potential. Concurrently, we observed depleted abundance of other bacteria whose predicted metagenomes suggest functional capacities to produce a variety of antiinflammatory compounds. Most strikingly, we found that resolution of these exacerbation-related changes in sputum microbiota composition differed significantly, depending on the exacerbation treatments prescribed. Treatment with corticosteroids resulted in microbiome enrichment for a number of bacterial communities, mostly members of the Proteobacteria phylum, whereas prolonged suppression of microbiota was seen in those treated with antibiotics alone. Taken together, our findings suggest that exacerbations of COPD are associated with heterogeneous changes in the bronchial microbiome, with increases in the abundance of species related to typical COPD pathogens and decreases in microbiota members that contribute to compositional and functional homeostasis. The findings further suggest that exacerbation treatments may have very different impacts on the bronchial microbiome’s rate of return toward baseline composition.